Effects of low-temperature treatments on surface hardness, retained austenite content, residual stress condition and the resulting tooth root bending strength of case-hardened 18CrNiMo7-6 gears. (November 2019) - Kratzer, D; Dobler, F; Tobie, T; Hoja, T; Steinbacher, M; Stahl, K
This paper contains parts of the research project FVA 612 and investigates the correlation between low-temperature treatments of case-hardened gears made from the material 18CrNiMo7-6 and the resulting surface hardness, retained austenite content, and residual stress condition. These parameters were further investigated with regard to the tooth root bending strength obtained with pulsating test rigs. The tested gears were subjected to various low-temperature treatments including different temperature levels before or after tempering. Other investigated parameters were the application of a shot blasting treatment and the effect of low-temperature treatments on gears with increased retained austenite content after the carburizing process.